Channel Auctions - Azevedo, Eduardo M.; Pennock, David M.; Waggoner, Bo; Weyl, E. Glen (Management Science, 2020)
Standard auction formats feature either an upper bound on the equilibrium price that descends over time (as in the Dutch auction) or a lower bound on the equilibrium price that ascends over time (as in the English auction). We show that in some settings with costly information acquisition, auctions featuring both (viz., a narrowing channel of prices) outperform the standard formats. This Channel auction preserves some of benefits of both the English (truthful revelation) and Dutch (security for necessary information acquisition) auctions. Natural applications include housing, online auction sites like eBay, recording transactions on blockchains, and spectrum rights. This paper was accepted by Joshua Gans, business strategy.